Community Empowerment through the Use of Roptar as a Child Development Stimulation Tool - Rita Yulifah; Tri Johan Agus Y (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The Corona Virus Disease 2019 (Covid-19) outbreak has had a major impact on all aspects of life, the implications of the pandemic are not only on the socio-economic aspects but also have an impact on the health sector1. The health impact is not only felt by parents but also on children. The impact of the covid pandemic on children can take place in the short, medium and long term. Children are hidden victims of the covid-19 pandemic. The impact of the Covid-19 pandemic on children includes problems with immunization, social mental problems, and child development, especially in the personal social aspect. 2 Out of 80 million children in Indonesia, around 30% of children have the opportunity to experience serious and various impacts due to the pandemic. 3 This community service activity carried out to assist the Community Health Center program in conducting Detection Stimulation Activities, Early Developmental Intervention (SDIDTK) carried out by Kindergarten Teachers or PAUD Teachers. In carrying out the assistance, Kindergarten teachers and PAUD teachers use educational media which is a representation of the SDIDTK book in the form of a Rotating Wheel educational game tool (hereinafter abbreviated as ROPTAR) specifically for health promotion efforts, SDIDTK which can be done by Kindergarten teachers or PAUD teachers. So it is hoped that the companion can provide SDIDTK optimally based on appropriate and fun references. Posttest evaluation results of 93.33% target knowledge in the good category exceeds the target indicator set ≥ 80%. Community empowerment through increasing knowledge about stimulation of child development is seen as one of the important points in empowering the community for early detection of child development6. ROPTAR is an interesting alternative media besides the Developmental Pre Screening Questionnaire (KPSP) as a tool for stimulating child development8, this is indicated by the response to using ROPTAR getting the lowest score of 9.5 out of the highest score of 10.